Pharmacokinetics and Dosimetry Studies for Optimization of Pretargeted Radioimmunotherapy in CEA-Expressing Advanced Lung Cancer Patients - Bodet-Milin, Caroline; Ferrer, Ludovic; Rauscher, Aurore; Masson, Damien; Rbah-Vidal, Latifa; Faivre-Chauvet, Alain; Cerato, Evelyne; Rousseau, Caroline; Hureaux, José; Couturier, Olivier; Salaün, Pierre-Yves; Goldenberg, David M.; et al. (Frontiers in Medicine, 2015)
Objectives A phase I pretargeted radioimmunotherapy trial (EudractCT 200800603096) was designed in patients with metastatic lung cancer expressing carcinoembryonic antigen (CEA) to optimize bispecific antibody and labeled peptide doses, as well as the delay between their injections. Methods Three cohorts of three patients received the anti-CEA × anti-histamine-succinyl-glycine (HSG)-humanized trivalent bispecific antibody (TF2) and the IMP288 bivalent HSG peptide. Patients underwent a pretherapeutic imaging session S1 (44 or 88 nmol/m2 of TF2 followed by 4.4 nmol/m2, 185 MBq, of 111In-labeled IMP288) and, 1–2 weeks later, a therapy session S2 (240 or 480 nmol/m2 of TF2 followed by 24 nmol/m2, 1.1 GBq/m2, of 177Lu-labeled IMP288). The pretargeting delay was 24 or 48 h. The dose schedule was defined based on preclinical TF2 pharmacokinetic (PK) studies, on our previous clinical data using the previous anti-CEA-pretargeting system, and on clinical results observed in the first patients injected using the same system in Netherlands. Results TF2 PK was represented by a two-compartment model in which the central compartment volume (Vc) was linearly dependent on the patient’s surface area. PK was remarkably similar, with a clearance of 0.33 ± 0.03 L/h/m2. 111In- and 177Lu-IMP288 PK was also well represented by a two-compartment model. IMP288 PK was faster (clearance 1.4–3.3 L/h). The Vc was proportional to body surface area, and IMP288 clearance depended on the molar ratio of injected IMP288 to circulating TF2 at the time of IMP288 injection. Modeling of image quantification confirmed the dependence of IMP288 kinetics on circulating TF2, but tumor activity PK was variable. Organ-absorbed doses were not significantly different in the three cohorts, but the tumor dose was significantly higher with the higher molar doses of TF2 (p < 0.002). S1 imaging predicted absorbed doses calculated in S2. Conclusion The best dosing parameters corresponded to the shorter pretargeting delay and to the highest TF2 molar doses. S1 imaging session accurately predicted PK as well as absorbed doses of S2, thus potentially allowing for patient selection and dose optimization. Trial Registration ClinicalTrials.gov NCT01221675 (EudractCT 200800603096).